2020
DOI: 10.37575/b/agr/2117
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sewage Sludge Use for Cultivation of some Plants and its Effects on some Soil Properties at Al Ahsa

Abstract: Wastewater treatment plants produce a large amount of sludge, which negatively affects our environment. The agricultural application of sludge is an environmentally friendly disposal option. The current study investigated the use of sewage sludge in the fertilisation of arid land in Al Ahsa, KSA, to reduce the need for importing fertilisers and increase plant productivity. Sewage sludge was used as an organic fertiliser in the cultivation of cucumber (Cucumis sativa) and lettuce (Lactuca sativa) through its sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Phosphate and nitrate were positively correlated (p < 0.01) with correlation coefficients of r = 0.30. The current study revealed relatively higher values of phosphate and nitrate measured in treated wastewater used in irrigation, which could improve the soil fertility of semiarid land [20]. Nitrate and ammonium had a weak, but significant, negative correlation (r = 0.28, p < 0.01).…”
Section: Correlation Between Irrigation Water Quality Variablesmentioning
confidence: 56%
See 3 more Smart Citations
“…Phosphate and nitrate were positively correlated (p < 0.01) with correlation coefficients of r = 0.30. The current study revealed relatively higher values of phosphate and nitrate measured in treated wastewater used in irrigation, which could improve the soil fertility of semiarid land [20]. Nitrate and ammonium had a weak, but significant, negative correlation (r = 0.28, p < 0.01).…”
Section: Correlation Between Irrigation Water Quality Variablesmentioning
confidence: 56%
“…Hence, the main sources of irrigation water in Al-Ahsa Oasis are currently groundwater wells mixed with both treated wastewater and partially agricultural drainage water. Approximately 200,000 m 3 /day of treated wastewater used in irrigation derives from main sewage treatment plants (STPs) in Al-Ahsa, namely Hofuf STP, Umran STP, Oyun STP, and Aramco STP [20]. These sewage treatment plants use both primary, secondary, and tertiary treatment processes along with the use of an aerobic activated sludge method.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Land application of the sludge is a traditional disposal option because it offers the possibility of recycling plant nutrients, providing organic material, improving soil fertilit y along with physical properties and enhancing crop yield [6,7]. The organic fraction in organic amendments can enhance significantly soil, water infiltration, microbial activity, structure, and water holding capacity and it can reduce soil compaction and erosion [8]. Chemical properties such as electrical conductivity (EC), organic carbon, and soil pH may also be improved by organic amendments application [9].…”
Section: Introductionmentioning
confidence: 99%